Impact of Teachers' Demographics on Total Quality Management Parameters-The Case of Primary Education - Nikolaos Kaiseroglou; Eleni Sfakianaki; Maria Koemtzi (MDPI AG, 2023)
The purpose of this paper is to highlight the application of TQM in primary education (PE) by exploring teachers' views and, more specifically, by examining the impact of their demographic data on their attitude towards TQM. A study was conducted among teachers in Greek public primary schools with the aim being to investigate their views on seven TQM parameters. The study used a structured questionnaire that was positively evaluated for validity and reliability. In total, 2088 completed questionnaires were collected, and non-parametric tests were employed. The results reveal statistically significant differences among groups of respondents based on gender, job-position, educational level, age, and years of experience in PE, as well as geographical location of the school. The study provides real-time empirical evidence of TQM in PE, enriching the existing literature, which lacks empirical and validated data from the PE level. The data revealed by the study indicate differences in perception of the TQM concept and its application among the participants, and their response should be further analysed to explore the reasons that generate them and, thus, facilitate the initiation of TQM practices within a PE school environment.